Factibilidad en la instalación de una planta extractora de jugo y aceite esencial de naranja (Citrus Sinensis) en el cantón Tosagua - Bravo Ormaza, Diego Orlando (2014)
This research aimed to establish the feasibility of an extraction plant juice and essential oil of orange (Citrus sinensis) in Tosagua city. A market study was conducted at a segment of the population between 15 and 64 years was conducted old at the Portoviejo canton where the level of acceptance of the product is 92.69%, which is projected to Manta, Chone, Bolívar, Rocafuerte and Tosagua cities where total demand exceeds 2.657.984,56 kg, in other words, 2.658 t orange juice; which aims to capture 30% for the first year of operations. The technical study established the minimum processing capacity of 7,16 t daily business in considering the application of technologies to maximize yields of juice and orange essential oil. The Leopold matrix applied in the environmental impact study estimated low adversity, where the generation of solid waste and waste water are the most important environmental impacts. The initial investment established a net present value (NPV) of $ 183.481,40, the internal rate of return (IIR) 36,29% and payback period on investment (PPB) 2 years, 4 months and 12 days. The results determined that there is a potential consumer segment willing to buy orange juice packaging, while imports of orange essential oil can be covered and gradually replaced by domestic production. The project is technically, environmentally, economically and financially viable.